2019
DOI: 10.1105/tpc.19.00155
|View full text |Cite
|
Sign up to set email alerts
|

A Photosynthesis-Specific Rubredoxin-Like Protein Is Required for Efficient Association of the D1 and D2 Proteins during the Initial Steps of Photosystem II Assembly

Abstract: Oxygenic photosynthesis relies on accessory factors to promote the assembly and maintenance of the photosynthetic apparatus in the thylakoid membranes. The highly conserved membrane-bound rubredoxin-like protein RubA has previously been implicated in the accumulation of both PSI and PSII, but its mode of action remains unclear. Here, we show that RubA in the cyanobacterium Synechocystis sp PCC 6803 is required for photoautotrophic growth in fluctuating light and acts early in PSII biogenesis by promoting the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 77 publications
10
42
0
Order By: Relevance
“…Consistent with these results, pulse labeling and pulse-chase experiments showed that newly synthesized PSII core subunits are mainly present in the PSII RC, pre-CP43, and pre-CP47 intermediates after labeling for 20 min and an additional 30-min chase (Figure 3B). These results confirm that RBD1 is required for PSII assembly in vivo (García-Cerdán et al, 2019;Kiss et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with these results, pulse labeling and pulse-chase experiments showed that newly synthesized PSII core subunits are mainly present in the PSII RC, pre-CP43, and pre-CP47 intermediates after labeling for 20 min and an additional 30-min chase (Figure 3B). These results confirm that RBD1 is required for PSII assembly in vivo (García-Cerdán et al, 2019;Kiss et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Enzymatic digestion of the Ycf48 gel band was performed by chymotrypsin and Asp-N protease as described in [ 33 ]. MALDI spectra were measured using SolariX XR™ FT-ICR mass spectrometer (Bruker Daltonics, Billerica, MA, USA) operating with mass accuracy better than 3 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the use of nickel affinity chromatography for the purification of His-CP47 complexes results most probably in isolating a mixture of His-CP47m, His-RC47 and His-PSII(1). The subsequent analysis of the preparation using CN PAGE or glycerol density centrifugation also resulted in partial detachment of loosely bound CP43m from PSII(1) (see, for instance Kiss et al 2019) and the putative NRC complex in fact consists of a mixture of isolated His-CP47m and CP43m detached from the isolated His-PSII(1).…”
Section: Discussionmentioning
confidence: 99%